2020
DOI: 10.3390/ijerph17062008
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Minimization Analysis of a Medical Record-based, Store and Forward and Provider-to-provider Telemedicine Compared to Usual Care in Catalonia: More Agile and Efficient, Especially for Users

Abstract: Background: Telemedicine (interconsultation between primary and hospital care teams) has been operating in the counties of Central Catalonia Bages, Moianès and Berguedà since 2011, specializing in teledermatology, teleulcers, teleophthalmology and teleaudiometries. For the period until the end of 2019, a total of 52,198 visits were recorded. Objective: To analyze the differential costs between telemedicine and usual care in a semi-urban environment. Methodology: A cost-minimization evaluation, including direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The facilities offered by digital health tools, combined with a gradual decline in the cost of gadgets to comparatively insignificant levels, open the door to a set of possibilities for cost-effective interventions in the field of health. The result of this work fits in with other studies that point to the positive economic impacts of telemedicine [ 30 , 31 ]. In the context of COVID-19, these possibilities make even more sense insofar as they can reduce travel, social contact, and consequently intrahospital infections [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…The facilities offered by digital health tools, combined with a gradual decline in the cost of gadgets to comparatively insignificant levels, open the door to a set of possibilities for cost-effective interventions in the field of health. The result of this work fits in with other studies that point to the positive economic impacts of telemedicine [ 30 , 31 ]. In the context of COVID-19, these possibilities make even more sense insofar as they can reduce travel, social contact, and consequently intrahospital infections [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although not specifically referring to patients with DM, a local study has shown that telemedicine could save up to €15 per visit. Patients are the greatest beneficiaries of these savings (owing to shorter waiting time and travel costs) but it is also more efficient from the healthcare perspective [ 54 ]. The added benefits of telemedicine in the era of the COVID-19 crisis and lockdown, for patients, healthcare professional and the healthcare system, cannot be disregarded, even though they are not the focus of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[24]. Advantages include convenience, low cost and ready accessibility of health-related information and communication using the Internet and other associated technologies [25].…”
Section: Telemedicine and Telehealthmentioning
confidence: 99%